Extracellular bioelectrical lexicon: detecting rhythmic patterns within dermal fibroblast populations - Rute C. Félix; Maria C. Medeiros; Youssef Elamine; Deborah M. Power; Henrique Leonel Gomes (Scientific Reports)
Abstract This study uses a bioelectronic-based method to establish how non-electrogenic cells, like dermal fibroblast, employ bioelectrical signals to convey information. Electrophysiology using large-area Multielectrode Arrays (MEAs) devices revealed how populations of non-electrogenic cells in vitro generate patterns of bioelectrical signals. The period of the bioelectrical patterns depends on cell population activity. In a fully formed, healthy monolayer, bioelectrical activity is minimal. But during the formation of a monolayer, signals appear randomly, with a dominant period of 4.2 min. Occasionally, quasi-periodic bursts occur with a period between 1.6 and 2 min. When a mechanical wound is inflicted and during subsequent monolayer repair, quasi-periodic signal bursts occur, with an average period ranging from 60 to 110 min. The study uncovers a short-range non humoral communication system and a lexicon of bioelectrical signals linked to cell states.